Pengembangan Lembar Kerja RME dengan Konteks Maritim untuk Menguatkan Kemampuan Komunikasi Matematis - Sari, Rupita Mina; Arifin, Sujinal; Komarudin, Komarudin (Edumatica : Jurnal Pendidikan Matematika, 2025)
This study aims to develop an RME-based worksheet for integer learning that meets the standards of validity and practicality. It has a potential effect on students' mathematical communication skills. This development research adopts the ADDIE stages, including analysis, design, development, implementation, and evaluation. The research participants involved 33 grade VII students at SMPN 33 Palembang. Data was collected through validation sheets, practicality sheets were assessed using a Likert scale of 1–5, and mathematical communication ability tests were evaluated based on scoring guidelines. Based on the results of the analysis, the worksheets developed reached a level of validity with an average score of 4.36 (very valid category). Initial practicality tests through one-to-one and small groups showed that the category was very practical, so the product was declared feasible for implementation. The results of the practicality test at the implementation stage also showed an average score of 4.60 (very practical category). The potential effect can be seen from the achievement of an average mathematical communication ability test score of 80.30 after the implementation of the worksheet (very good category). Thus, it can be concluded that the worksheet meets the aspects of validity and practicality and provides the expected potential effect.